1995
DOI: 10.1007/bf00241975
|View full text |Cite
|
Sign up to set email alerts
|

Responses of guinea pig primary vestibular neurons to clicks

Abstract: Responses of single neurons in the vestibular nerve to high-intensity clicks were studied by extracellular recording in anaesthetised guinea pigs. One hundred and two neurons in the posterior division of the superior branch or in the inferior branch of the vestibular nerve were activated at short latency by intense clicks. The latency of activation was short (median 0.9 ms) and the threshold was high: the click intensity for evoking the response of these cells was around 60 dB above the auditory brainstem resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
207
0
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 326 publications
(226 citation statements)
references
References 18 publications
12
207
0
7
Order By: Relevance
“…According to Broussard et al (1995), the median latency of crossed, excitatory response was 1.5 ms. Given the 0.9 ms median latency of click-evoked responses of vestibular afferents (Murofushi et al 1995), the 2.55 ms median latency of click-evoked crossed, excitatory response of abducens neurons is consistent with the activation of the disynaptic direct VOR pathways. Fourth, we compared the latencies of abducens neurons and the second order vestibular nuclei neurons to ipsilateral clicks.…”
Section: Click Activates Both Canal and Otolith Vor Pathwayssupporting
confidence: 56%
See 1 more Smart Citation
“…According to Broussard et al (1995), the median latency of crossed, excitatory response was 1.5 ms. Given the 0.9 ms median latency of click-evoked responses of vestibular afferents (Murofushi et al 1995), the 2.55 ms median latency of click-evoked crossed, excitatory response of abducens neurons is consistent with the activation of the disynaptic direct VOR pathways. Fourth, we compared the latencies of abducens neurons and the second order vestibular nuclei neurons to ipsilateral clicks.…”
Section: Click Activates Both Canal and Otolith Vor Pathwayssupporting
confidence: 56%
“…This may be justified by the conservative nature of the vestibular peripheral end organs. According to Murofushi et al (1995), the minimum latency of clickevoked vestibular afferent response was 0.4 ms in guinea pigs, which was very close to the 0.33 ms minimum latency of short electric pulse-evoked vestibular afferent response in squirrel monkeys (Goldberg et al 1984). The extreme short latency is one of the most prominent features of acoustic activation of the vestibular system, but we know little about how it occurs.…”
Section: Click Activates Both Canal and Otolith Vor Pathwaysmentioning
confidence: 71%
“…VEMPs are proposed to be generated via a disynaptic pathway, beginning in the saccular macula, then via the inferior vestibular nerve, lateral vestibular nucleus, medial vestibulospinal tract, and finally terminating on the motor neurons of the SCM muscle [4][5][6]. Through the efforts during past decade, VEMPs have been validated to reflect the sacculo-collic reflex, and widely used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the origins of the cVEMP responses have yet to be elucidated. In contrast to the earlier reports that identified the saccule as the sole source of the cVEMPs (Murofushi et al 1995;Todd et al 2000), recent animal studies have demonstrated sound sensitivity in vestibular afferents from the semicircular canals and the utricle (Zhou et al 2004(Zhou et al , 2005(Zhou et al , 2007Xu et al 2009;Zhu et al 2011 and2014). Our recent human study (Wei et al 2013) also showed that cVEMP frequency tuning curves are better modeled as a summation of two mass spring systems with resonance frequencies of 300 and 1000 Hz.…”
Section: Introductionmentioning
confidence: 52%